Groundwater Analysis Using Vertical Electrical Sounding and Water Quality Tester in Sukolilo Area, Surabaya, East Java: Significant Information for Groundwater Resources - Bahri, Fuad Aulia; Rismayanti, Hasibatul Farida; Warnana, Dwa Desa (Institut Teknologi Sepuluh Nopember, 2017)
This research purpose to find out groundwater quality and environmental pollution that has occurred in aquifer of Sukolilo, Surabaya, East Java. Vertical Electrical Sounding is a geoelectric method to measure the resistivity of the rocks. This instruments is used to obtain subsurface information about aquifer depth.Â Water quality tester is used to know water quality by measuring acidity, conductivity, salinity, Oxidation Reduction Potential, and Total Dissolved Solid parameter. The result shows that aquifer has about 3.17 m thickness and lied at 0.45 to 3.62 m with lithology of alluvium. Lithology changes toward the north shown by different depth of the layers of rock. There has been sea water intrusion in groundwater aquifer at Sukolilo area. It was shown by high salinity and high Total Dissolved Solid parameter of some water samples with the higher values approaching sea. Therefore, it can be concluded that water from the unconfined aquifer in Sukolilo was polluted and not worthy for consumption.